Design of Monitoring Device for the Process of Organic Waste Decomposition into Compost Fertilizer and Plant Growth through Smartphones based on Internet of Things Smart Farming - Haris Isyanto; Jumail Jumail; Rahayu Rahayu; Nofian Firmansyah (Journal of Electrical Technology UMY, 2021)
Based on data published by the Ministry of Living Environment and Forestry in 2020, Indonesia produces at least 93,200 tons of waste per day in various types of composition or around 34 million tons of waste per year. From the collection of waste, it could be used as compost fertilizer which is taken from leaf waste. From these problems, a device was designed that could monitor the decomposition process of organic waste into compost fertilizer. This device is equipped with a temperature sensor, humidity sensor, sensor of soil pH, soil moisture sensor, and color sensor to monitor the composting fertilizer process. The device could also detect plant growth as an indication that the compost fertilizer made is in good condition. Our device was used on the Internet of Things (IoT) and the blynk application as a monitoring application. From the test results, the temperature sensor's accuracy is 98.2%, the humidity sensor is 96.1%, the soil pH sensor is 95.26%, the soil moisture sensor is 98.55%, and the color sensor successfully detects the results of plant growth well. The design of this device is expected to invite the public to be wiser in sorting waste and using it for the surrounding environment.